PELATIHAN PENERAPAN SANITASI HYGIENE DAN PENENTUAN UMUR SIMPAN PRODUK OLAHAN RUMPUT LAUT PADA KELOMPOK PENGOLAH RUMPUT LAUT DI DESA AENG DAKE KABUPATEN SUMENEP PROVINSI JAWA TIMUR - Abdillah, Annur Ahadi; Monica Sahidu, Adriana; Saputra, Eka; Yuli Pujiastuti, Dwi (Universitas Mataram, 2025)
Sumenep Regency is one of the contributors to seaweed production in Indonesia and is classified as a Minapolitan location. One of the seaweed producing districts is Aeng Dake Village, Bluto District. The problem that arises for both partners is that there is no food safety system, namely a sanitation and hygiene system. Both partners still produce processed products on a small scale and are not yet standardized in the field of food safety. This problem means that the product cannot compete with other products that have implemented food safety. The second problem is that in producing processed products, partners cannot determine the shelf life. The problem of the food safety system, namely sanitation and hygiene, can be solved by providing training on the concept of sanitation and hygiene including theory and practical application in the production process flow. The problem of determining shelf life can be solved by training in determining shelf life including theory and practice that can predict product shelf life. The practice of implementing hygiene sanitation and determining shelf life was given to the processing group by providing theory and simulations of the application of the material in the process of making noodle products, crackers, juice and seaweed sticks. Training provides skills in analyzing and determining the shelf life of products independently.